Implementasi Triple Helix Of Economic Education Terintegrasi Sustainable Develompent Goals (SDGS) Untuk Meningkatkan Hardskill Dan Softskill Mahasiswa Pendidikan Ekonomi Berbasis Kampus Merdeka Di Universitas Hamzanwadi - Jailani, Huzain; Rapii, Muhammad (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The implementation of the independent campus learning policy encourages the learning process in higher education to become more autonomous and flexible. This research focuses on the aim of implementing a triple helix of integrated economic education with sustainable development goals (SDGs) to improve the hard skills and soft skills of independent campus-based economic education students at Hamzanwadi University. This research uses a qualitative research method which is field research (field research). Data collection techniques were carried out through observation, interviews and documentation techniques. Data analysis includes data collection, data condensation, data presentation, and conclusions. The findings of this research apply the triple helix of economic education that is integrated with sustainable development goals (SDGs) to improve hard skills and soft skills that are adapted to the Independent Campus concept. Students are given challenges and opportunities to develop creativity, capacity, personality and student needs, as well as develop independence in seeking and finding knowledge through field realities and dynamics such as ability requirements, real similarities, social interaction, collaboration, self-management, performance demands, targets and his achievements.